Latitudinal distribution of auroral kilometric radiation based on Polar spacecraft observations - Louis, C. K.; Smith, K. D.; Jackman, C. M.; Fogg, A. R.; Waters, J. E.; O'Dwyer, E. P.; Granroth, L. (My University, 2023)
Auroral Kilometric Radiation (AKR) is a terrestrial radio emission that occurs above the poles. It is produced by the cyclotron maser instability at frequencies close to the electron cyclotron frequency (proportional to the magnetic field amplitude). The Polar orbiter sampled radio emissions from pole to pole for two years, thus AKR emissions were sampled across a broad range of latitudes. This is important because the frequency and visibility of AKR emissions depend on observer latitude. In order to distinguish AKR emissions from other radio sources present in the Polar dataset, we used the \SPectrogram Analysis and Cataloguing Environment" (SPACE) labelling tool to create a labeled catalogue, focusing initially on 45 days of Polar data, but laying the ground for future examination of this rich dataset, including the application of machine learning approaches using our labels as a training set to classify a broader range of data. From this catalogue we derived occurrence and intensity distributions relative to frequency and observer latitude. These distributions allow constraints to be put on the viewing effects, which is critical to enable robust study of the underlying physics of AKR emission.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED